Radius survey of crawler crane base on total station. Issue 1 (July 2020) - Xu, Haixiang; Qiu, Jun; Wu, Fengqi; Xue, Jiai
Abstract: The process of surveying crane parameters has been continually refined due to the competitive situation, modern surveying instruments and more powerful softwares. As the radius is the crucial parameter to determine the jib crane's safety, a survey scheme is put forward to solve the problem that the rotary axis can't be determined on-site in the paper, which measures the coordinate data of marked points by utilizing the total station, then the plane fitting method and the space analytic geometry method are adopted to determine the revolving centre axis. The proposed method is simple and easy to implement with acceptable accuracy in the field.